Vehicular engine design - Hoag, Kevin; Dondlinger, Brian (New York Springer, 2006)
This book provides an introduction to the design and mechanical development of reciprocating piston engines for vehicular applications.
Includes index
Keywords: Công nghệ kỹ thuật ô tô